Reaching Across Distance and Hardship: An Interview with Riad - Davis, Tatum; Makinde, Peter (WritingThreeSixty, 2025)
I encountered Riad on TikTok, the video based social media platform, when interacted with my posts in August 2024. On 10 August I was the first to say hello because he had started following me and liked many of my videos. I did not expect this interaction to result in any kind of friendship, but over time, I have come to care deeply about Riad and his family. At the time, I was aware of the genocide taking place in Palestine, but I did not feel personally implicated by it – to me, it was a distant conflict in a distant land. Since learned to internalise Nelson Mandela’s message that none of us are free until all of us are free in some unique and very personal ways. Riad, like many TikTok users from Palestine, asked if I could help him by donating a sum of money because his source of income was lost, and the needs of his family increased. To make sure that this man was honest, I asked him for a video call via another social media platform, WhatsApp. He showed me the tent in which he lives with his wife and three children. I decided to donate 50 to help Riad and his family, and since then we have grown very close. We chat almost every day, making sure that he and his family are safe, and he loves sending me pictures of him and his children, and what they eat. I’ve come to know Riad as a kind-hearted man with a strong sense of family and love for his children. The following interview shows us glimpses of his daily life, and how he has experienced the genocide. With this interview, I hope to encourage others to find friends in conflict zones like Gaza, and not only extend a helping hand financially, but also to get to know them as people with families and dreams. This interview was conducted via WhatsApp at the convenience of Riad. He does not speak English and used a translator to be sure that we can understand him.